Selective JAK2 pathway inhibition enhances anti-leukemic functionality in CD19 CAR-T cells - Kohei Mitsuno; Masaya Suematsu; Yuki Naito; Azusa Mayumi; Hideki Yoshida; Shinya Osone; Toshihiko Imamura; Yozo Nakazawa; Shigeki Yagyu; Tomoko Iehara (Cancer Immunology, Immunotherapy)
Abstract The integration of molecular targeted therapeutics with chimeric antigen receptor T (CAR-T) cell therapy represents a novel strategy to amplify the anti-tumor efficacy of immunotherapy. While CD19-targeted CAR-T cells and Janus kinase (JAK) inhibitors have independently shown efficacy against certain B-cell leukemias, such as Philadelphia chromosome-like acute lymphoblastic leukemia, the concurrent use of JAK1/2 inhibitors, such as ruxolitinib, has been implicated in reducing CAR-T cell potency by inhibiting the JAK1-dependent T cell activation pathway. This study explores the combinatorial use of a selective type II JAK2 inhibitor, CHZ868, with CD19 CAR-T cells, revealing a synergistic enhancement of anti-leukemic activity across B-cell tumor models irrespective of JAK2 mutational status. CHZ868-mediated JAK2 inhibition did not induce the exhaustion of CAR-T cells, maintaining efficacy over repeated tumor challenges and significantly extending survival in mouse models engrafted with JAK2 inhibitor-resistant leukemia cells (median survival, CD19 CAR-T + CHZ868 vs. CD19 CAR-T + DMSO: 32 days vs. 26 days, p = 0.0303). Transcriptomic analyses suggest that CHZ868 impedes CAR-T cell differentiation while preserving their proliferative capacity, a crucial factor in maintaining CAR-T cell functionality. Therefore, the selective inhibition of the JAK2 pathway may potentiate CAR-T cell therapy and offer a viable treatment strategy for patients with resistant B-cell leukemias.